2017
DOI: 10.1155/2017/1324310
|View full text |Cite
|
Sign up to set email alerts
|

Evidences of the Low Implication of Mosquitoes in the Transmission ofMycobacterium ulcerans, the Causative Agent of Buruli Ulcer

Abstract: Background Buruli ulcer (BU) continues to be a serious public health threat in wet tropical regions and the mode of transmission of its etiological agent, Mycobacterium ulcerans (MU), remains poorly understood. In this study, mosquito species collected in endemic villages in Benin were screened for the presence of MU. In addition, the ability of mosquitoes larvae to pick up MU from their environment and remain colonized through the larval developmental stages to the adult stage was investigated. Methods 7,218 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Before DNA extraction, MU-free fecal materials from domesticated Capra aegagrus hircus (a female goat) were spiked with MU Agy99 pure culture strain and tested for MU-extraction protocol and validation. Contaminations and controls were managed as described previously [17,37].…”
Section: Molecular Analyses Extraction Of Genomic Dnamentioning
confidence: 99%
See 1 more Smart Citation
“…Before DNA extraction, MU-free fecal materials from domesticated Capra aegagrus hircus (a female goat) were spiked with MU Agy99 pure culture strain and tested for MU-extraction protocol and validation. Contaminations and controls were managed as described previously [17,37].…”
Section: Molecular Analyses Extraction Of Genomic Dnamentioning
confidence: 99%
“…Quantitative PCR analysis MU molecular DNA-diagnosis targets (IS2404, IS2606, and KR-B) were screened from genomic DNA-extracts using the TaqMan qPCR protocol described by Fyfe et al [38]. Positivity for MU and the cycle threshold cutoffs were defined using the Cts-method (ΔCts [IS 2606 -IS 2404 ]) as established previously [37,38]. Multilocus VNTR typing and sequence analysis were also performed as additional confirmatory tests for MU.…”
Section: Molecular Analyses Extraction Of Genomic Dnamentioning
confidence: 99%
“…A few experimental laboratory studies also failed to confirm the implication of mosquitoes as biological agents for the transmission of M. ulcerans [ 38 , 39 •]. In a study by Djouaka et al, ingestion of M. ulcerans was observed during the larvae stage of the mosquitoes but not during both pupae and adult stages, revealing the low ability of infected or colonized mosquitoes to vertically transmit M. ulcerans to their offspring [ 40 ]. Interestingly, a recent study by Wallace et al demonstrated and proposed that a micro-puncture in the skin from any cause, whether from insect bites, injuries, or other natural means, has the potential to inject M. ulcerans from the environment into the skin and generate ulcers [ 39 •].…”
Section: Uncovering the Mode Of Transmissionmentioning
confidence: 99%
“…ulcerans in the aquatic environment primarily infects humans via existing minor skin trauma but could be inoculated mechanically by insect vectors through either infected arthropod saliva or transfer of M. ulcerans on the skin surface into the bite wound. However, except perhaps for sporadic cases [32], evidence for a vector role for biting aquatic bugs (or mosquitoes [103]) in BU transmission in nature is weak [23]. flight.…”
Section: Discussionmentioning
confidence: 99%